Marital Age, Cigarette Exposure, Physical Activity, Sleep Duration, and Prenatal Depression - Azniah Syam; Ashar HM; Eva Arna Abrar; Asriah Syam (Universitas Ahmad Dahlan, 2022)
Background: Extensive studies indicate that prenatal depression disrupts a woman's life and has a detrimental effect on the mother-child and further breastfeeding. Numerous factors associated with nutrition, physical activity, sleep patterns, and exposure to cigarette smoke are strongly suspected of contributing to the dysregulation of hormones associated with depression. This study aims to examine the association between physical activity, nutritional status, prior exposure to cigarette smoke, and the risk of prenatal depression. Method: A cross-sectional study was conducted on 79 pregnant women at the Pampang Primary Healthcare Center between January and March 2021. Using chi-square and multiple logistic regression, identify the risk factors that most significantly contribute to the risk of prenatal depression. Result: Married under the age of 19th (p<0.039), inactive daily exercise (p<0.023), inadequate sleep duration (p<0.045), and mothers who have been exposed to cigarette smoke for more than a year (p<0.001) all increased the risk of prenatal depression. Cigarette exposure, contributes most, with a 5.4-fold increased risk of developing mental disorders while breastfeeding. Conclusion: It is critical for health services to include early screening for prenatal depression during antenatal care as a means of preventing future breastfeeding difficulties, particularly in mothers with vulnerability.